Solid-state electrolyte membrane, preparation method thereof and solid-state battery

By accommodating inorganic solid electrolyte particles with high spherical shape in the porous matrix, a solid electrolyte membrane with high density and flexibility characteristics was prepared, which solved the problem of large flexibility and porosity of the solid battery electrolyte membrane, and improved the cycling and rate performance of the battery.

CN119695260APending Publication Date: 2025-03-25QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411843015.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The solid electrolyte membrane of solid state batteries is poor in flexibility and has a large porosity, which affects the long-term use and rate performance of the battery, and the ion transmission performance decreases after adding a flexible substrate.

Method used

A porous matrix is ​​used as a carrier to accommodate inorganic solid electrolyte particles with high spherical shape, and particles are prepared by ball milling, and a solid electrolyte membrane is laid and pressed on the porous matrix.

Benefits of technology

The density and ionic conductivity of the solid electrolyte membrane are improved, the flexibility of the membrane is enhanced, and the circulation and rate performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188371160000161
    Figure BDA0005188371160000161
  • Figure BDA0005188371160000171
    Figure BDA0005188371160000171
Patent Text Reader

Abstract

The invention relates to a solid electrolyte membrane, a preparation method thereof and a solid-state battery. The solid electrolyte membrane comprises a porous matrix and solid electrolyte particles accommodated in through holes of the porous matrix; the solid electrolyte particles meet the condition that the sphericity of at least 80% of the solid electrolyte particles meets the condition that phi is larger than or equal to 0.8 and smaller than 1; the solid electrolyte particles are inorganic solid electrolyte particles. The sphericity degree of the solid electrolyte particles is regulated and controlled, the quality of the solid electrolyte particles contained in the porous matrix in the unit area is improved, the density and ionic conductivity of the solid electrolyte membrane are improved, meanwhile, due to the existence of the porous matrix, it is ensured that the solid electrolyte membrane has good flexibility, and the service life of the solid electrolyte membrane is prolonged. Therefore, the cycle performance of the solid-state battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a solid electrolyte membrane and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries have attracted widespread attention due to their high safety, but there are some problems in actual use of solid-state batteries. The solid-state electrolyte membrane that simply includes solid electrolyte particles has poor flexibility and large porosity, which is not conducive to the long-term use of the battery. Adding a flexible substrate to the solid-state electrolyte membrane will significantly reduce the ion transport performance of the solid-state electrolyte membrane, which is not conducive to the battery's rate performance.

[0003] Therefore, there is an urgent need for a solid electrolyte membrane having both good flexibility and ion transport capability and a solid-state battery prepared from the electrolyte membrane. Summary of the invention

[0004] Based on this, in response to the above problems, the present application provides a solid electrolyte membrane and a preparation method thereof, and a solid-state battery to solve the above technical problems.

[0005] A first aspect of the present application provides a solid electrolyte membrane, the solid electrolyte membrane comprising a porous substrate and solid electrolyte particles contained in the through holes of the porous substrate;

[0006] Furthermore, the solid electrolyte particles satisfy: at least 80% of the inorganic solid electrolyte particles have a sphericity of satisfy:

[0007] The solid electrolyte particles are inorganic solid electrolyte particles.

[0008] In one embodiment, the particle size D50 of the solid electrolyte particles is 1-10 μm.

[0009] In one embodiment, the solid electrolyte is a halide solid electrolyte.

[0010] In one embodiment, the porous matrix is ​​one or more of non-woven fabric, aramid film, polyolefin film, cellulose film, glass fiber cloth or melt-blown cloth.

[0011] In one embodiment, the porosity of the porous matrix is ​​60%-95%.

[0012] In one embodiment, the thickness of the porous matrix is ​​10-100 μm.

[0013] In one embodiment, the solid electrolyte membrane further includes a binder.

[0014] In one embodiment, the mass ratio of the binder to the solid electrolyte particles is (0.1-3):(97-99.9).

[0015] In one embodiment, the porosity of the solid electrolyte membrane is 0.1%-5%.

[0016] The second aspect of the present application provides a method for preparing a solid electrolyte membrane as provided in the first aspect, comprising the following steps:

[0017] S1. preparing solid electrolyte particles;

[0018] The solid electrolyte particles satisfy the following requirements: at least 80% of the solid electrolyte particles have a sphericity of satisfy:

[0019] S2. Preparing a solid electrolyte membrane: laying a raw material including at least solid electrolyte particles on one side surface of a porous substrate, and pressing to form a solid electrolyte membrane.

[0020] In one embodiment, step S1 includes preparing solid electrolyte particles by ball milling.

[0021] A third aspect of the present application provides a solid-state battery, which includes the solid-state electrolyte membrane provided in the first aspect above.

[0022] Compared with traditional technologies, the solid electrolyte membrane of the present application has the following advantages: as the sphericity of the solid electrolyte particles increases, the porous matrix can accommodate more solid electrolyte particles and the solid electrolyte particles are more evenly distributed in the porous matrix. Therefore, the prepared solid electrolyte membrane has a higher density and a higher ionic conductivity. At the same time, due to the presence of the porous matrix, the solid electrolyte membrane is ensured to have good flexibility. DETAILED DESCRIPTION

[0023] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0024] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0026] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0027] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100-150nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).

[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0030] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0032] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0033] Solid-state batteries have attracted widespread attention due to their high safety, but there are some problems in actual use of solid-state batteries. The solid-state electrolyte membrane that simply includes solid electrolyte particles has poor flexibility and large porosity, which is not conducive to the long-term use of the battery. Adding a flexible substrate to the solid-state electrolyte membrane will significantly reduce the ion transport performance of the solid-state electrolyte membrane, which is not conducive to the battery's rate performance.

[0034] Based on this technical problem, this application provides the following technical solutions:

[0035] In a first aspect, the present application provides a solid electrolyte membrane, the solid electrolyte membrane comprising a porous substrate and solid electrolyte particles contained in through holes of the porous substrate;

[0036] Furthermore, the solid electrolyte particles satisfy: at least 80% of the solid electrolyte particles have a sphericity of satisfy: Including but not limited to 0.8, 0.85, 0.9, 0.95.

[0037] The solid electrolyte particles are inorganic solid electrolyte particles.

[0038] It can be understood that the sphericity of the solid electrolyte particles is defined here: the diameter of the "circle equal to the projected area of ​​the solid electrolyte particles" is set as d1, and the diameter of the "circle equal to the circumference of the projection of the solid electrolyte particles" in the same projection direction is set as d2,

[0039] It is understood that the at least 80% here refers to the particle ratio. Specifically, a certain number of solid electrolyte particles are weighed, and a scanning electron microscope test is performed to select several regions, and IMAGE J is used to calculate the sphericity of each electrolyte particle in each region, the number of particles that meet the sphericity requirements, and the total number of particles, and calculate their ratio.

[0040] As the sphericity of the solid electrolyte particles increases, the porous matrix can accommodate more solid electrolyte particles and the distribution of the solid electrolyte particles in the porous matrix is ​​more uniform. Therefore, the density of the prepared solid electrolyte membrane is higher; the ionic conductivity of the prepared solid electrolyte membrane is higher. At the same time, due to the presence of the porous matrix, the solid electrolyte membrane is ensured to have good flexibility.

[0041] The inorganic solid electrolyte particles include at least one of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte.

[0042] In one embodiment, the oxide solid electrolyte includes any one of garnet ceramic, LISICON-type oxide, NASICON-type oxide or perovskite ceramic, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of garnet ceramic and LISICON-type oxide, a combination of LISICON-type oxide and NASICON-type oxide, or a combination of LISICON-type oxide, NASICON-type oxide and perovskite ceramic.

[0043] In one embodiment, the garnet ceramic includes Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 or Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 Any one or a combination of at least two of the following, typical but non-limiting combinations include Li 6.5 Ln3Z 1.75 Te 0.25 O 12 With Li7La3Zr2O 12 The combination of Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 With Li 6.25 Al 0.25 La3Zr2O 12 A combination of, or Li 6.25 Al 0.25La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 与Li 6.75 La3Zr 1.75 Nb 0.25 O 12 的组合。

[0044] In one embodiment, the LISICON-type oxide includes Li 14 Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1) or Li 3+x Ge x V 1-x O4 (where 0 < x < 1), any one or a combination of at least two of them. Typical but non-limiting combinations include the combination of Li 14 Zn(GeO4)4 and Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), the combination of Li 3+x (P 1-x Si x )O4 (where 0 < x < 1) and Li 3+ x Ge x V 1-x O4 (where 0 < x < 1), or the combination of Li 14 Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1) and Li 3+x Ge x V 1- x O4 (where 0 < x < 1).

[0045] In one embodiment, the NASICON-type oxide can be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in some variants, the NASICON-type oxide can be selected from those including Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Yx Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, or a combination of any one or at least two of them. Typical but non - limiting combinations include the combination of LAGP and LATP, the combination of LYZP and Li 1.3 Al 0.3 Ti 1.7 (PO4)3, or the combination of LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3 and LiHf2(PO4)3.

[0046] In one embodiment, the perovskite - type ceramic includes Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1. 3Ta 1.7 O9, Li 2x-y Sr 1- x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25), or a combination of any one or at least two of them. Typical but non - limiting combinations include the combination of Li 3.3 La 0.53 TiO3 and LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75) and Li 3 / 8Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, or Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9 and Li3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3 combination.

[0047] In one embodiment, the sulfide solid electrolyte includes Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、(1-x)P2S 5-x Any one or a combination of at least two of Li2S (where 0.5≤x≤0.7), typical but non-limiting combinations include Li2S-P2S5 and Li2S-P2S5-MS x (where M is a combination of Si, Ge and Sn and 0≤x≤2), Li3.4 Si 0.4 P 0.6 S4 and Li 10 GeP2S 11.7 O 0.3 Combination of Li7P3S 11 、Li9P3S9O3 and Li 10.35 Si 1.35 P 1.65 S 12 A combination of, or Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 With Li(Si 0.5 Sn 0.5 ) s S 12 combination.

[0048] In one embodiment, the general formula of the halide solid electrolyte is Li x MX y N z , wherein 1≤x≤4, 4≤y+nz≤8, and n is the absolute value of the valence of N. The metal element M includes at least one of V, Cr, Mn, Zn, Cd, Fe, Pb, In, Y, Al, Sc, La, Lu, Ga, Zr, or Hf. X includes at least one of the halogen elements F, Cl, Br, and I. N is at least one of the non-metallic elements O and S. Exemplarily, the halide solid electrolyte includes Li3InBr 6-m Cl m (0≤m≤6), LiInX4, Li3YX6, Li3ErX6, Li3ScX6, Li3LaX6, Li 3-m Er 1-m Zr m Cl6(x≤0.6), Li 3-m Y 1-m Zr m Cl6(m≤0.6), Li3Y 1-m In m Cl6(0 <m<1)、Li2ZrX6、Li2ZrX y Oz(0<z≤1,y+z=6)、Li2ZrX y A mixture of one or more of Sz (0<z≤1, y+z=6).

[0049] In one embodiment, the particle size D50 of the solid electrolyte particles is 1 to 10 μm, including but not limited to 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm. By controlling the particle size and sphericity of the solid electrolyte particles, it is beneficial for the solid electrolyte particles to enter the pores of the porous matrix, which can effectively improve production efficiency and reduce the number of pressing times.

[0050] In a preferred embodiment, the solid electrolyte is a halide solid electrolyte. On the one hand, compared with existing solid electrolytes, halide solid electrolyte particles have high ionic conductivity, and on the other hand, compared with other inorganic solid electrolyte particles, Young's modulus is lower, which is conducive to the regulation of sphericity.

[0051] In a preferred embodiment, the halide solid electrolyte includes Li2ZrCl6, Li2ZrCl5F, Li2ZrCl 5.5 O 0.25 、Li3InCl6、Li3YCl6、Li2H f Cl6、LiInBr 4、 At least one of Li3InBr6, Li3LaI6, Li3LuCl6.

[0052] Of course, in other embodiments, other inorganic solid electrolyte particles may also be used as long as they meet the requirements.

[0053] In one embodiment, the porous matrix is ​​one or more of non-woven fabric, aramid film, polyolefin film, cellulose film, glass fiber cloth or melt-blown cloth.

[0054] In one embodiment, the porosity of the porous matrix is ​​60% to 95%, including but not limited to 60%, 65%, 70%, 75%, 80%, 85%, 90%, and 95%.

[0055] In one embodiment, the thickness of the porous matrix is ​​10-100 μm, including but not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm.

[0056] In one embodiment, the solid electrolyte membrane further includes a binder.

[0057] In one embodiment, the mass ratio of the binder to the solid electrolyte particles is (0.1-3):(97-99.9), including but not limited to 0.1:99.9, 0.2:99.8, 0.5:99.5, 0.8:99.2, 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97.

[0058] In a preferred embodiment, the mass ratio of the binder to the solid electrolyte particles is (0.1-1):(99-99.9).

[0059] The role of the binder is to further increase the bonding ability between the solid electrolyte particles and the porous matrix, and to prevent the solid electrolyte particles from escaping from the side of the porous matrix away from the raw material laying direction during the pressing process.

[0060] If there is too much binder, it will first take up a certain amount of space, which is not conducive to filling more solid electrolyte particles in the porous matrix and is not conducive to improving the lithium ion transmission capacity of the solid electrolyte membrane.

[0061] In one embodiment, the binder is a fiberizable binder, that is, the binder can be transformed from a granular state to a fiber state under a high shear force.

[0062] In one embodiment, the fiberizable binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.

[0063] In one embodiment, the porosity of the solid electrolyte membrane is 0.1%-5%, including but not limited to 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.

[0064] In some embodiments, every 1 cm 2 The mass of the raw material contained in the porous matrix is ​​3mg to 7mg.

[0065] The method for measuring the mass of solid electrolyte particles contained in a unit volume of a porous matrix is ​​as follows: measure the total mass of the raw materials M1 (in mg), scrape off the excess raw materials on the surface of the porous matrix, measure the mass of the excess raw materials M2 (in mg), measure the surface area S of the porous matrix (in cm 2 ), (M1-M2) / S, then every 1cm 2 The mass of raw material contained in the porous matrix.

[0066] The present application improves the mass of solid electrolyte particles contained in a porous matrix per unit area by regulating the sphericity and particle size of the solid electrolyte particles, thereby effectively improving the density and ionic conductivity of the solid electrolyte membrane.

[0067] The second aspect of the present application provides a method for preparing a solid electrolyte membrane as in the first aspect, comprising the following steps:

[0068] S1. preparing solid electrolyte particles;

[0069] The solid electrolyte particles satisfy the following requirements: at least 80% of the solid electrolyte particles have a sphericity of satisfy:

[0070] S2. Preparing a solid electrolyte membrane: laying a raw material including at least solid electrolyte particles on one side surface of a porous substrate, and pressing to form a solid electrolyte membrane.

[0071] In one embodiment, step S1 includes preparing solid electrolyte particles by ball milling.

[0072] In one embodiment, in step S1, the temperature of the ball milling treatment is -50°C to 25°C, including but not limited to -50°C, -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, and 25°C.

[0073] In one embodiment, the rotation speed of the ball milling treatment is 500 r / min to 800 r / min, including but not limited to 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min, and 800 r / min.

[0074] In one embodiment, the ball milling time is 4 h to 12 h, including but not limited to 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, and 12 h.

[0075] In one embodiment, the ball-to-material ratio of the ball milling process is 15:1 to 25:1, including but not limited to 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, and 25:1.

[0076] In one embodiment, step S2 further includes performing preliminary filling after laying the raw materials.

[0077] The initial filling is to vibrate or use a flexible roller to fill and distribute the raw materials.

[0078] In one embodiment, the method of preliminary filling is to place the solid electrolyte membrane intermediate in a vibrating chamber of a vibrating machine and vibrate to transfer the raw materials into the pores of the porous matrix to obtain the solid electrolyte membrane intermediate.

[0079] In one embodiment, the preliminary filling is to use a flexible roller such as a sponge roller to perform preliminary filling and redistribution of the raw materials in the pores of the porous substrate to obtain a solid electrolyte membrane intermediate.

[0080] It is understood that the initial filling mentioned in the present application includes the redistribution process of the raw materials on the surface of the porous matrix. The initial filling is conducive to the uniform distribution of the raw materials on the surface of the porous matrix, improves the uniformity of the material dispersion in the solid electrolyte membrane, and is conducive to improving the quality of the solid electrolyte particles filled in the porous matrix layer per unit area.

[0081] In one embodiment, in step S2, the pressure of the pressing treatment is 2t to 3t, including but not limited to 2t, 2.1t, 2.2t, 2.3t, 2.4t, 2.5t, 2.6t, 2.7t, 2.8t, 2.9t, and 3t.

[0082] In one embodiment, the pressing treatment time is 0.5 min to 5 min, including but not limited to 0.5 min, 1 min, 2 min, 3 min, 4 min, and 5 min.

[0083] In one embodiment, when a binder is used, a step of mixing the solid electrolyte particles with the binder is further included before step S2.

[0084] In one embodiment, when a fiberizable binder is used, the step of mixing the solid electrolyte particles with the binder and fiberizing the solid electrolyte particles is further included before step S2.

[0085] A third aspect of the present application provides a solid-state battery comprising the solid electrolyte membrane as claimed in claim 1 .

[0086] Solid-state batteries also include a positive electrode and a negative electrode.

[0087] In one embodiment, the positive electrode includes a positive electrode plate, a positive electrode tab is extended from the positive electrode plate, and the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer formed on the current collector.

[0088] The positive electrode active material layer includes a positive electrode active material, which is a compound capable of reversibly intercalating and deintercalating lithium.

[0089] In one embodiment, the positive electrode active material comprises one or more transition metal cations, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V) and combinations thereof.

[0090] In one embodiment, the positive electrode active material is one of a layered oxide, a spinel, and a polyanion. For example, the layered oxide (e.g., a rock salt layered oxide) comprises one or more lithium-based positive electrode active materials selected from the group consisting of LiCoO2 (LCO), LiNi x Mn y Co 1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi 1-x-y Co x Al y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-xO2 (where 0≤x≤1), and LiMO2 (where M is one of Mn, Ni, Co and Al and 0≤x≤1). The spinel contains one or more lithium-based positive active materials selected from the group consisting of LiMn2O4 (LMO) and LiNixMn 1.5 O4. The olivine type contains one or more lithium-based positive electrode active materials LiMPO4 (wherein M is at least one of Fe, Ni, Co and Mn). The polyanion cation contains, for example, phosphates such as LiV2(PO4)3 and / or silicates such as LiFeSiO4.

[0091] In one embodiment, the mass percentage of the positive electrode active material contained in the positive electrode active material layer can be 50wt% to 97wt%, such as 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 97wt%, etc., preferably 80wt% to 90wt%.

[0092] In one embodiment, the positive electrode further includes a positive electrode binder, which is used to bind components such as the positive electrode active material, the positive electrode conductive material, and the positive electrode current collector together. Specifically, the positive electrode binder includes a fiberized binder. Preferably, the fiberized binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.

[0093] In one embodiment, the mass percentage of the positive electrode binder contained in the positive electrode active material layer may be 1 wt% to 20 wt%, such as 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, etc., preferably 1.2 wt% to 10 wt%.

[0094] In one embodiment, the positive electrode also includes a positive electrode conductive material, which is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular limitation on it in the embodiments of the present application, as long as it has conductivity without causing chemical changes. Specifically, the positive electrode conductive material may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the positive electrode conductive material may preferably be carbon black.

[0095] In one embodiment, the specific surface area of ​​the positive electrode conductive material can be 80 m 2 / g~200m 2 / g, preferably 100m 2 / g~150m 2 / g.

[0096] In one embodiment, the mass percentage of the positive electrode conductive material contained in the positive electrode active material layer may be 1 wt% to 20 wt%, such as 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, etc., preferably 1.2 wt% to 10 wt%.

[0097] In one embodiment, the thickness of the positive electrode active material layer may be 30 μm to 400 μm, for example 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm to 110 μm.

[0098] In one embodiment, the positive electrode plate also includes a halide solid electrolyte, and the mass proportion of the halide solid electrolyte can be 1wt% to 50wt%, for example, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 30wt%, 40wt%, 50wt%, etc., preferably 10wt% to 20wt%.

[0099] In one embodiment, the positive electrode plate can be prepared by a dry method, that is, the positive electrode active material, the positive electrode conductive material, the halide solid electrolyte, and the positive electrode binder are mixed. The positive electrode active material, the positive electrode conductive material, and the halide solid electrolyte are mixed first, and then the positive electrode binder is added. Under the action of high shear force, the binder is converted from a powder state to a fibrous state to bond the positive electrode active material, the positive electrode conductive material, and the halide solid electrolyte together, and the positive electrode active material layer is formed by rolling.

[0100] In one embodiment, the solid-state battery further includes a negative electrode plate, wherein a negative electrode tab is extended from the negative electrode plate.

[0101] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector, wherein the negative electrode active material layer includes at least a negative electrode active material and a negative electrode binder.

[0102] In one embodiment, a carbon material can be selected as the negative electrode active material, and specifically one or more of the following can be selected: graphite, needle coke, amorphous carbon, a carbon-containing mesophase, carbon fiber, and a carbon material with a low degree of graphitization. Among them, graphite can include natural graphite, artificial graphite, etc. In addition, materials obtained by coating them with carbon materials, such as amorphous carbon and graphitized materials, can also be used. Amorphous carbon includes but is not limited to particles obtained by firing the entire mesophase, and particles obtained by infusible treatment and firing of a carbon precursor. As carbonaceous particles with a low degree of graphitization, particles obtained by firing organic matter at a temperature generally below 2500°C can be listed.

[0103] In addition, non-metallic materials that can be used as negative electrode active materials also include silicon and its compounds, such as Si, SiOx (0≤x<2). Since silicon-containing materials are prone to expansion, easy to fall off from the negative electrode current collector, and have poor conductivity, they are often mixed with carbon materials, such as core-shell structures containing carbon coating layers.

[0104] In one embodiment, the mass percentage of the negative electrode active material contained in the negative electrode active material layer can be 80wt% to 99wt%, for example, 80wt%, 85wt%, 90wt%, 95wt%, 97wt%, 99wt%, etc., preferably 95wt% to 97wt%.

[0105] In one embodiment, when the negative electrode active material is a non-metallic material such as a carbon material, the negative electrode binder may be an aqueous binder such as one or more of sodium hydroxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymer, cyclodextrin, etc.;

[0106] In one embodiment, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry. The negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying. The thickener can generally be used to adjust the viscosity of the slurry.

[0107] In one embodiment, the thickener may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.

[0108] In one embodiment, the mass proportion of the thickener in the negative electrode slurry can be 0.1wt% to 5wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc., preferably 0.5wt% to 3wt%, and more preferably 0.6wt% to 2wt%.

[0109] It is understood that the above examples of positive and negative electrodes are only illustrative, and any known positive electrode active material, positive electrode binder, positive electrode conductive material, negative electrode active material, negative electrode binder, and negative electrode conductive material can be used in the present application without violating the inventive concept of the present application. And the addition of known additives based on actual use requirements should also be considered within the scope of protection of the present application.

[0110] The present application will be further described below with reference to specific embodiments and comparative examples.

[0111] Example 1

[0112] The solid electrolyte particles (Li2ZrCl6) are ball-milled to obtain a first material, and the sphericity of the first material is The ball milling temperature is 0℃, the speed is 700r / min, the time is 12h, and the ball-to-material ratio is 15:1.

[0113] Among them, 85% of the solid electrolyte particles have a spherical shape. satisfy: is 0.9.

[0114] The raw material is laid on one side of the porous substrate and a preliminary filling treatment is performed to obtain a solid electrolyte membrane intermediate. The raw material includes a first material and a fiberizable binder PTFE, and the mass ratio of the first material to PTFE is 99:1. The porous substrate is a non-woven fabric with a porosity of 85% and a thickness of 20 μm.

[0115] The pressing process was performed under a pressure of 2.5 t, for a time of 1.5 min, and at a temperature of 120°C.

[0116] Example 2

[0117] The difference between this embodiment and embodiment 1 is that the sphericity of the first material is different.

[0118] Example 3

[0119] The difference between this embodiment and embodiment 1 is that the sphericity of the first material is different.

[0120] Example 4

[0121] The difference between this embodiment and embodiment 1 is that the particle size of the first material is different.

[0122] Example 5

[0123] The difference between this embodiment and embodiment 1 is that the particle size of the first material is different.

[0124] Example 6

[0125] The difference between this embodiment and embodiment 2 is that the type of solid electrolyte is different.

[0126] Example 7

[0127] This embodiment differs from Embodiment 1 in that the raw material does not include a fiberizable binder.

[0128] Comparative Example 1

[0129] The difference between this comparative example and Example 1 is that the sphericity of the first material is not adjusted.

[0130] The test parameters of the embodiments and comparative examples are summarized in Table 1 below:

[0131] Table 1

[0132]

[0133] Preparation of solid-state batteries

[0134] The positive electrode, solid electrolyte membrane and negative electrode are stacked and assembled to obtain a solid-state battery. The positive electrode is NCM811 and the negative electrode is graphite.

[0135] Test Case

[0136] The ionic conductivity and porosity of the solid electrolyte membranes prepared in the above examples and comparative examples were measured. The results are shown in Table 2 below.

[0137] The utilization rate of the raw materials during the preparation of the above examples and comparative examples was measured, and the utilization rate of the raw materials refers to the ratio of the mass of the raw materials entering the porous matrix to the mass of the laying raw materials. The results are shown in Table 2 below.

[0138] The cycle performance of the battery comprising the solid electrolyte membrane prepared in the above examples and comparative examples was measured. The results are shown in Table 2 below.

[0139] Table 2

[0140]

[0141] By comparing Examples 1 to 7 and Comparative Example 1, the utilization rate of the raw materials can be effectively improved by adjusting the sphericity of the solid electrolyte particles, that is, more solid electrolyte particles can enter the through holes of the porous matrix. Therefore, the ionic conductivity and density of the solid electrolyte membrane can be effectively improved, and the cycle performance of the battery prepared thereby can be improved.

[0142] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane includes a porous matrix and solid electrolyte particles contained in the through holes of the porous matrix; The solid electrolyte particles satisfy: at least 80% of the solid electrolyte particles have a sphericity φ that satisfies: 0.8≤φ<1; The solid electrolyte particles are inorganic solid electrolyte particles.

2. The solid electrolyte membrane according to claim 1, characterized in that The particle size D50 of the solid electrolyte particles is 1 μm to 10 μm.

3. The solid electrolyte membrane according to claim 1, characterized in that The solid electrolyte particles are halide solid electrolyte particles.

4. The solid electrolyte membrane according to claim 1, characterized in that The porous matrix is ​​one or more of non-woven fabric, aramid film, polyolefin film, cellulose film, glass fiber cloth or melt-blown cloth.

5. The solid electrolyte membrane according to claim 1, characterized in that The porosity of the porous matrix is ​​60%-95%.

6. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the porous matrix is ​​10 μm-100 μm.

7. The solid electrolyte membrane according to claim 1, characterized in that The solid electrolyte membrane also includes a binder.

8. The solid electrolyte membrane according to claim 1, characterized in that The porosity of the solid electrolyte membrane is 0.1%-5%.

9. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 8, characterized in that: The steps include: S1. preparing solid electrolyte particles: the solid electrolyte particles satisfy: at least 80% of the solid electrolyte particles have a sphericity φ that satisfies: 0.8≤φ<1; S2. Preparing a solid electrolyte membrane: laying a raw material including at least the solid electrolyte particles on one side surface of a porous substrate, and pressing to form a solid electrolyte membrane.

10. A solid-state battery, characterized in that: Comprising the solid electrolyte membrane according to any one of claims 1 to 8.

Citation Information

Cited By

  • Difunctional composite lithium-conducting diaphragm as well as preparation method and application thereof

    CN120955309A